The Use of Context Clues in Teaching Economic English Vocabulary for Development Economics Students - Adys, Himaya Praptani; Adys, Himala Praptami (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study investigates the effectiveness of context clue strategies in teaching economic English vocabulary (English for Specific Purposes/ESP) for Development Economics students at Universitas Negeri Makassar. Using a quantitative pre-experimental approach (one-group pre-test post-test design), 109 students (31 male, 78 female) aged 18-20 years with English proficiency ranging from basic to intermediate participated in the study. Data were collected through economics-based vocabulary tests administered before and after eight instructional sessions. Paired samples t-test analysis revealed a statistically significant improvement from pre-test (M = 52.37, SD = 8.94) to post-test (M = 74.18, SD = 7.62), t(108) = 42.07, p < .001, Cohen's d = 2.44 (very large effect). Pearson correlation analysis indicated a strong positive relationship between context clue ability and vocabulary gain (r = .612, p < .001). These findings imply that explicit context clue instruction significantly benefits all proficiency groups, with the basic group showing the highest relative gain. This study supports the integration of context clue strategies into economics ESP curricula.